KEMAMPUAN LITERASI MATEMATIKA SISWA SMA DALAM MENYELESAIKAN SOAL HOTS SPLTV DITINJAU DARI SELF-REGULATED LEARNING - Murtikusuma, Randi Pratama; Pambudi, Didik Sugeng; Wahdana, Akfi Hikmah (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
This study was conducted to describe and describe the mathematical literacy ability of students of class X IPA 1 SMA Negeri Arjasa in solving HOTS questions in terms of self-regulated learning on the material of the Three Variable Linear Equation System (SPLTV). The type of research used in this research is descriptive qualitative. In order to determine students' mathematical literacy skills in terms of self-regulated learning, the students' self-regulated learning levels were first grouped. There are three levels of self-regulated learning, namely students with low, medium and high self-regulated learning. For each level of self-regulated learning, 1 person was selected to be the subject of the study. So that 3 research subjects were selected, namely 1 student with a low level of self-regulated learning (S1), 1 student with a moderate level of self-regulated learning (S2), and 1 student with a high level of self-regulated learning (S3). Each subject was given a HOTS test question on the material of the Three Variable Linear Equation System (SPLTV) and continued with interviews to determine the fulfillment of indicators at each level of mathematical literacy ability that could be achieved by the subject. Based on the analysis that has been done, S1 is not able to meet the four indicators at level 4 of mathematical literacy ability, S2 is only able to meet one indicator of mathematical literacy ability at level 4, and S3 is able to meet all four indicators at level 4 of mathematical literacy ability and does not reach the next level. ABSTRAK Penelitian ini dilakukan untuk mendeskripsikan dan menggambarkan kemampuan literasi matematika siswa kelas X IPA 1 SMA Negeri Arjasa dalam menyelesaikan soal HOTS  ditinjau  dari self-regulated learning pada materi Sistem Persamaan Linear Tiga Variabel (SPLTV). Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Untuk mengetahui kemampuan literasi matematika siswa ditinjau dari self-regulated learning, terlebih dahulu dilakukan pengelompokan tingkatan self-regulated learning siswa. Tiga tingkatan self-regulated learning yaitu siswa dengan self-regulated learning rendah, sedang dan tinggi. Masing-masing tingkat self-regulated learning dipilih 1 orang untuk dijadikan subjek penelitian. Sehingga terpilih 3 subjek penelitian yaitu 1 siswa dengan tingkatan self-regulated learning rendah (S1), 1 siswa dengan tingkatan self-regulated learning sedang (S2), dan 1 siswa dengan tingkatan self-regulated learning tinggi (S3). Masing-masing subjek diberikan soal tes HOTS pada materi Sistem Persamaan Linear Tiga Variabel (SPLTV) dan dilanjutkan dengan wawancara untuk mengetahui pemenuhan indikator pada setiap level kemampuan literasi matematika yang dapat dicapai oleh subjek. Berdasarkan analisis yang telah dilakukan S1 tidak mampu memenuhi keempat indikator pada level 4 kemampuan literasi matematika, S2 hanya mampu memenuhi satu indikator kemampuan literasi matematika pada level 4, dan S3 mampu memenuhi keempat indikator pada level 4 kemampuan literasi matematika dan tidak mencapai level berikutnya.